Unveiling the Role of FinTech in Advancing Sustainable Development Goals: A Structural Equation Modeling Approach - Patil, Yogita Madhukar; Bhatnagar, Namit; Banarjee, Shourya (International Journal of Engineering and Management Research, 2025)
The integration of financial technology (FinTech) into modern economic systems has sparked significant interest regarding its potential to accelerate progress toward the United Nations Sustainable Development Goals (SDGs). This study investigates the structural relationship between FinTech adoption and five selected SDGs—Economic Growth, Quality Education, Gender Equality, Reduced Inequalities, and Climate Action—mediated through Financial Inclusion and Digital Literacy. Using a Structural Equation Modeling (SEM) framework, we surveyed participants across diverse socio-economic backgrounds to assess how FinTech-driven financial inclusion and digital capability influence sustainable development outcomes. The model reveals that Digital Literacy is the strongest mediating factor, significantly enhancing Economic Growth (β = 0.904), Quality Education (β = 0.829), and Reduced Inequalities (β = 0.859). In contrast, Financial Inclusion plays a more moderate yet targeted role, particularly in addressing inequality and gender-based financial access. These findings suggest that while FinTech infrastructure is foundational, its real developmental impact is realized through empowerment mechanisms—especially digital literacy. Policymakers and stakeholders are urged to focus on user education and inclusivity when deploying FinTech solutions to ensure alignment with global sustainability objectives.